Oral manifestations of granulomatosis with polyangiitis - Clinical and radiological assessment - Katarzyna Szczeklik; Anna Włudarczyk; Katarzyna Wawrzycka-Adamczyk; Jacek Górka; Maria Fuks-Kulska; Dagmara Darczuk; Jolanta Pytko-Polończyk; Wojciech Szczeklik (Elsevier, 2019)
Background/purpose: Granulomatosis with polyangiitis (GPA) is a type of primary systemic vasculitis associated with the presence of anti-neutrophil cytoplasmic antibodies (ANCA). GPA mainly affects medium and small vessels and may manifest in different organs, most commonly upper respiratory tract. Oral lesions occur in 6-13% of GPA patients and might be the first symptom observed by the patient. This study presents the evaluation of orofacial manifestations of patients with GPA. Materials and methods: Prospective study was conducted between June 2014 and November 2017 in Department of Allergy and Immunology at University Hospital in Krakow. Patients diagnosed with GPA, after medical assessment, were examined including precise dental inspection, bacterial and fungal flora of oral cavity evaluation and Cone Beam Computed Tomography (CBCT) imaging. Results: Nine patients were enrolled in the study. Characteristic for GPA strawberry gingivitis was observed in one patient. Bone destruction and inflammatory lesions in paranasal sinuses was confirmed by CBCT in 55.6% of patients. Fungal infection was revealed in 66.7% of patients. Conclusion: These findings oblige dentists to consult patient with laryngologist or internal medicine physician to establish further diagnostic approach, because early diagnosis of GPA is crucial for implementing appropriate treatment and preventing chronic organ damage. Keywords: ANCA, Gingivitis, Granulomatosis with polyangiitis, Oral mucosa, Vasculitis